Deep Pacific storage of respired carbon during the last ice age: Perspectives from bottom water oxygen reconstructions. (15th February 2020) - Jacobel, A.W.; Anderson, R.F.; Jaccard, S.L.; McManus, J.F.; Pavia, F.J.; Winckler, G.
Abstract: Reconstructions of past changes in dissolved oxygen concentrations in the abyssal ocean are of interest to paleoceanographers because of their potential to help characterize and quantify the transfer of carbon between the atmosphere and the deep ocean. This potential, derived from the stoichiometric relationship between oxygen consumption and the regeneration of organic matter, has recently been expanded by compilations of core top observations for two proxies: the δ 13 C gradient between coeval infaunal and epifaunal benthic foraminifera (Δδ 13 C), and biomarker preservation. Here, we review these newer proxies, and the more established redox proxy authigenic uranium (aU), to critically evaluate our understanding of the controls on proxy signal production and preservation. We locate our work in the equatorial Pacific, presenting both new data and a compilation of existing records from thirty-two sediment cores to draw semi-quantitative conclusions about bottom water oxygen and respired carbon concentrations over the last glacial period. We find that the biogeochemical limitations on these proxies may be more substantial than previously appreciated, and therefore suggest several best-practice recommendations for their application. Despite the recognized data limitations, the compilation identifies the glacial Pacific Ocean as a dominant sink for CO2 at all depths below the modern oxygen minimum zone. Our review emphasizes the importance of multiproxy reconstructions, informed by site-specific records of paleoproductivity, in drawing coherent, internally consistent conclusions about glacial ocean oxygenation and carbon storage. Highlights: Large swaths of the deep Pacific were more poorly oxygenated during the last glacial maximum, reflecting enhanced storage of respired carbon. Multiproxy reconstructions are key for correctly interpreting data. Flux-normalized records of marine export productivity are critical for disentangling the controls on bottom water oxygen records. The Δδ 13 C proxy is influenced by more variables than previously appreciated, and is therefore less quantitative.